(untitled) (Third Sector Social Economic Review, 2022)
In this study, an integrated model including CRITIC and CoCoSo procedures is proposed to evaluate whether the financial performance of the Turkish banking sector is affected by the pandemic crisis in the period covering the years 2016-2021. In the study, objective weights for the selected performance criteria were calculated with the help of the CRITIC procedure. Then, the financial performance of the Turkish banking sector in the period 2018-2021 is evaluated using the CoCoSo procedure. In accordance with the purpose of the study, firstly, ten financial performance indicators related to the banking sector are determined based on the previous literature. According to the results of the CRITIC procedure, the three criteria that have the most impact on the performance of the banking sector in the 2016-2021 period are the ratio of fees, commission and banking services income to total income, the ratio of legal capital to total risk-weighted assets, and the ratio of net interest income to average total assets. According to the results of the application of the CoCoSo method, the Turkish banking sector exhibited the worst financial performance in 2020, when the pandemic was most intense. This result reveals that the sector has been adversely affected by the pandemic crisis, that is, banks operating in the banking sector are unsuccessful in risk management. Therefore, this result provides important information to the mechanisms that regulate and supervise the banking sector in terms of designing long-term plans to ensure the steady growth of the sector. In addition, the findings also reveal that the performance of the sector tends to improve due to the measures taken against the COVID-19 pandemic in 2021.